Flight of the phoenix - LaFevers, R. L. (LaFevers, R. L. Nathaniel Fludd, beastologist, 2009)
In 1928, when timid ten-year-old Nate learns that his parents have been lost at sea, he joins his father's cousin on a flight to Arabia where they must oversee the death and rebirth of the phoenix, thus beginning his training as a "beastologist."